EFISIENSI USAHATANI BAWANG MERAH DI KABUPATEN BANTUL - , ROSROS ROSDIANTINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Shallots are horticultural commodities that have high economic value. In Bantul district of Yogyakarta province many farmers who depend on their income of shallots farming. For maximum income, the farmers are required to manage their farm efficiently both technical, allocative and economic. The purposes of this research are (1) To find out the variables that influence production of shallots farming in Bantul district, (2) To find out the variables that influence income of shallots farming in Bantul district, and (3) To find out the level of technical, allocative and economic efficiency of shallots farming in Bantul district. The stochastic frontier production function analysis, stochastic frontier cost function analysis, and multiple regression analysis for income function using OLS (Ordinary Least Square) were applied for analysis. Primary data are collected from shallots farmers. The result of the analysis shows that land area, seeds, Phonska fertilizers, fungicides and labor intensive significantly and positively affecting shallots farming production. Land area, seed prices, Phonska fertilizer price, fungicide prices and labor intensive significantly influencing on shallots farming income. Based on the analysis, the average economic efficiency of shallot farming is 0.82, which caused technical and allocatif inefficiency. Average level of technical efficiency and allocative efficiency are equal to 0.77 and 1.06.